2018
DOI: 10.1039/c7ra10706d
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal impact on structural and phonon properties of Er3+ and Tm3+ co-doped MY(WO4)2 (M = Li, Na, K) nanocrystals

Abstract: TEM images of NaY(WO4)2:Er, Tm nanocrystalline powders synthesized by the Pechini method after calcination at (a) 550 °C, (b) 600 °C and (c) 700 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Lately, another microwave-assisted hydrothermal synthesis method for the preparation of monoclinic KY(WO 4 ) 2 nanocrystals without using organic surfactants, has been proposed [ 50 ]. This reaction involves preheating at 388 K for 0.5 h, a reaction at 523 K for 3 h, a purification process with deionized water, and a drying process at 353 K for 20 h, after calcination at 1023 K for 1 h. The final product of the reaction shows a tendency towards agglomeration and irregular morphological habits.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, another microwave-assisted hydrothermal synthesis method for the preparation of monoclinic KY(WO 4 ) 2 nanocrystals without using organic surfactants, has been proposed [ 50 ]. This reaction involves preheating at 388 K for 0.5 h, a reaction at 523 K for 3 h, a purification process with deionized water, and a drying process at 353 K for 20 h, after calcination at 1023 K for 1 h. The final product of the reaction shows a tendency towards agglomeration and irregular morphological habits.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] In recent times, nanosized alkali metal ferrites have attracted increasing interest, as they exhibit distinct properties compared to their bulk counterparts with the same composition. [14][15][16][17] The synthesis of nanoparticles with controlled size, shape, and composition holds immense scientific and technological significance, promising groundbreaking advancements in various nanotechnology and medical fields. [18][19][20] Consequently, an emphasis on methodological aspects becomes crucial for the design and preparation of ferrite materials.…”
Section: Introductionmentioning
confidence: 99%
“…The rare-earth (RE) double tungstates of ARE­(WO 4 ) 2 (A = alkali metal ion) initially attracted attention for solid laser applications in the single-crystal form, because of their excellent mechanical, thermal, and chemical durability, the high value of the χ­( 3 ) nonlinear cubic susceptibility, their good Raman activity, the facile admittance of various RE 3+ activators, and the broad optical transparency from the visible to the near-infrared region. Later studies revealed that ARE­(WO 4 ) 2 tungstates (RE = La, Y, Gd, and Lu) are attractive hosts for luminescent purposes, , because these RE 3+ ions do not have absorption or emission in the visible light region and the compounds present self-activation of the WO 4 2– ligands, high optical absorption in the ultraviolet (UV) region, and efficient energy transfer from WO 4 2– to the activator. The potential application of ARE­(WO 4 ) 2 has been demonstrated in the multifaceted areas of bioimaging [PEG-NaGd­(WO 4 ) 2 :Eu], biosensors [Na­(Gd,Eu)­(WO 4 ) 2 ], photothermal therapy (PTT) [NaY­(WO 4 ) 2 :Sm 3+ /Nd 3+ ], photocatalysis, light-emitting diodes (LEDs) [NaGd­(WO 4 ) 2 :Pr 3+ ], and temperature sensing [NaY­(WO 4 ) 2 :Er 3+ /Yb 3+ ] …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of ARE­(WO 4 ) 2 compounds can be achieved by a number of methodologies, including solid-state reaction, sol–gel and Pechini-type sol–gel, molten salt growth, microwave-assisted processing , and hydrothermal/solvothermal reaction, , as also summarized in the review article by Kaczmarek and van Deun . Though the hydrothermal and solvothermal techniques are widely acknowledged to be capable of directly generating inorganic solids of controlled phase structure and crystallite morphology within a short amount of reaction time, they frequently yielded unknown products (precursors) for the RE 3+ –tungstate reaction system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation